1986
DOI: 10.21236/ada169024
|View full text |Cite
|
Sign up to set email alerts
|

UV/Ozone Cleaning of Surfaces

Abstract: FORT MONMOUTH, NEW JERSEY 07703-5302 NOTICES DisclaimersThe citation of trade names and names of manufacturers in this report is not to be construed as official Government indorsement or approval of commercial products or services referenced herein. Destruction NoticeDestroy this report when it is no longer needed. "itThe UV/ozone method, which is reviewed in this repo-Tt, is anefective method of removing a vat jety of contaminants from surfaces. It is a simlple-to-use dry process which is inexpensive to set u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The concentration reduces with increasing laser fluence (see Table 1 and Fig. 6), similarly to elsewhere reported [23]. Since the TOF-SIMS analysis shows only counts, XPS was adopted to obtain an absolute value of the carbon concentration.…”
Section: Stoichiometry and Chemical Compositionsupporting
confidence: 79%
“…The concentration reduces with increasing laser fluence (see Table 1 and Fig. 6), similarly to elsewhere reported [23]. Since the TOF-SIMS analysis shows only counts, XPS was adopted to obtain an absolute value of the carbon concentration.…”
Section: Stoichiometry and Chemical Compositionsupporting
confidence: 79%
“…The pair was then blown dry with nitrogen and promptly covered to minimize dust contamination. Following this, the pair was UV/ozone treated for 15minutes to remove carbonaceous contamination (24). Discs that did not have PFPE applied to them, and all bearing balls were put into a dry N2atmosphere within 5 minutes of the UV/ozone treatment where they stayed until tribo-tested.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…It has been suggested that UV irradiation cleans the polymer surface by removing the organic contamination and changing the molecule structure of the matrix polymer [15][16][17][18][19][20] , which modifies the surface tension. However, the wetting tension values of the matrix resins did not greatly change after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The silane coupling treatment can establish chemical bonding between the fiberglass of the FRC post and the core build-up materials. Plasma and UV irradiation are considered to clean surfaces by removing the organic contamination 11,15,16) , increasing the surface microroughness [16][17][18][19] , and changing the molecular structure of the surface area [16][17][18][19][20] . If the molecular structure of the matrix resin is changed, it is possible to create IPN bonding despite the thermoplastic polymers.…”
Section: Introductionmentioning
confidence: 99%